Phraseology in Two Slavic Valency Dictionaries: Limitations and Perspectives. (22nd February 2016) - Przepiórkowski, Adam; Hajič, Jan; Hajnicz, Elżbieta; Urešová, Zdeňka
Abstract: Phraseological components of valency dictionaries for two West Slavic languages are presented, namely, of the PDT-Vallex dictionary for Czech and of the Walenty dictionary for Polish. Both dictionaries are corpus-based, albeit in different ways. Both are machine-readable and employable by syntactic parsers and generators. The paper compares the expressive power of the phraseological subformalisms of these dictionaries, discusses their limitations and makes recommendations for their possible extensions, which can be possibly applied also to other valency dictionaries with rich phraseological components.